Interactions of N- and C-terminal parts of Ana1 permitting centriole duplication but not elongation - Agota Nagy; Levente Kovacs; Helene Rangone; Jingyan Fu; Mark Ladinsky; David M. Glover (Open Biology)
The conserved process of centriole duplication requires the establishment of a Sas6-centred cartwheel initiated by Plk4’s phosphorylation of Ana1/STIL. Subsequently, the centriole undergoes conversion to a centrosome requiring its radial expansion and elongation, mediated by a network requiring interactions between Cep135, Ana1/Cep295 and Asterless/Cep152. Here, we show that mutant alleles encoding overlapping N- and C-terminal parts of Ana1 are capable of intragenic complementation to rescue radial expansion. This permits the recruitment of Asl and thereby centriole duplication and mechanosensory cilia formation to restore the coordination defects of these mutants. This genetic combination also rescues centriole duplication in the male germ line but does not rescue the elongation of the triplet microtubule-containing centrioles of primary spermatocytes. Consequently, these males are coordinated but sterile. Such centriole elongation is rescued by the continuous, full-length Ana1 sequence. We define a region that when deleted within otherwise intact Ana1 does not permit primary spermatocyte centrioles to elongate but still allows recruitment of Asl. Our findings point to differing demands upon the physical organization of Ana1 for the distinct processes of radial expansion and elongation of centrioles.